Vitamin D deficiency and insufficiency among US adults: prevalence, predictors and clinical implications. Issue 8 (12th April 2018) - Liu, Xuefeng; Baylin, Ana; Levy, Phillip D.
Abstract: Vitamin D deficiency (VDD) and insufficiency (VDI) are increasing at a global level, and they are associated with increased risk of various diseases. However, little information is available on the prevalence and predictors of VDD and VDI in a representative population of US adults. Serum 25-hydroxyvitamin D (25(OH)D) measurements were collected from 26 010 adults aged ≥18 years from the National Health and Nutrition Examination Survey (NHANES) 2001–2010. Using thresholds recommended by the Endocrine Society, VDD was defined as 25(OH)D<50 nmol/l and VDI as 50≤25(OH)D<75 nmol/l. Weighted multinomial log-binomial regression was conducted to estimate prevalence ratios of VDD and VDI. The prevalences of VDD and VDI in 2001–2010 were 28·9 and 41·4 %, respectively. Adults who were black, less educated, poor, obese, current smokers, physically inactive and infrequent milk consumers had a higher prevalence of VDD. After adjustment for other potential predictors, obese adults showed 3·09 times higher prevalence of VDD and 1·80 times higher prevalence of VDI than non-obese adults. Physically inactive adults had 2·00 and 1·36 times higher prevalence of VDD and VDI than active peers. Compared with frequent consumers, rare consumers of milk had 2·44 and 1·25 times higher prevalence of VDD and VDI, respectively. Current alcohol drinkers had 38 % lower prevalence of VDD than non-drinkers. Awareness of the high prevalence of VDD and VDI among US adults and related predictors could inform behavioural and dietary strategies for preventing VDD and monitoring VDI, especially in old, black, obese and inactive individuals who report rare consumption of milk.